To explore the relation between green human resource management (GHRM) and the green supply chain (GSCM): Empirical evidence from industrial companies in Dhofar reign, Oman - Hubais A.; Awain A.B.; Jais J.; Atiya T. (American Institute of Physics Inc., 2023)
This research discusses the relationship between green human resource management and green supply chain management. A questionnaire was created for quantitative purposes. The questionnaire comprises 29 items divided in each variable. The respondents of the survey were 305 Employees from industrial companies in the Dhofar region participated in the study. Random probability sampling used. Using partial least squares analysis, four hypotheses were developed and analyzed. Results showed that green recruitment has significantly influences green supply chain. Green training has significantly affected the green supply chain management. Green performance appraisal has significantly affected to green supply chain management. Green encouragement has significantly effect the green supply chain management. 2022 Author(s).